The value of x that satisfies the equation lo g 2 ( 2 x − 1 + 3 x + 1 ) = 2 x − lo g 2 ( 3 x ) can be expressed as lo g a b . What is the value of a + b ?
Note : a and b are both fractions and their sum is an integer .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great solution, Deepanshu. I kept thinking that a and b had to be integers since a + b had to be an integer, so when I found a solution of 1 − lo g 2 ( 3 ) 1 I couldn't see how to get this in the form lo g a ( b ) where a and b were integers. Then it finally dawned on me that they might not be integers. :)
@Abhishek Singh Great question. One suggestion, though; you will need to specify that a and b are both fractions with denominator 2 , since otherwise the solution will not be unique. For instance,
lo g 2 3 ( 2 1 ) = lo g 4 9 ( 4 1 ) ,
and in the first case we have a + b = 2 and in the second a + b = 2 5 .
Log in to reply
Thanks sir, I'll change the wording .
Thanks Sir :)
lo g 2 ( 2 x − 1 + 3 x + 1 ) = lo g 2 ( 2 2 x ) − lo g 2 ( 3 x ) = lo g 2 ( 3 x 2 2 x )
2 x − 1 + 3 x + 1 = 3 x 2 2 x
3 x 2 x − 1 + 3 = 3 2 x 2 2 x = ( 3 2 ) 2 x
2 1 ( 3 2 ) x + 3 = ( 3 2 ) 2 x
2 ( 3 2 ) 2 x − ( 3 2 ) x − 6 = 0
( 2 ( 3 2 ) x + 3 ) ( ( 3 2 ) x − 2 ) = 0
( 3 2 ) x = 2 , − 2 3
Since a x > 0 ∀ x ∈ R , a > 0 , reject ( − 2 3 )
∴ ( 3 2 ) x = 2
x = lo g 3 2 2
Observe that lo g m n = lo g m 1 m lo g m 1 n = − 1 lo g m 1 n = − lo g m 1 n = lo g m 1 n 1 . Then
x = lo g 2 3 2 1
a + b = 2 3 + 2 1 = 2
Very neat and clear. But I stumbled over the last step. I would find it clearer if you inserted the line
2 1 = ( 2 3 ) x
lo g 2 2 x − 1 + 3 x + 1 = 2 x − lo g 2 3 x
Let m = 2 x and n = 3 x
Simplifying the above expression we get:
2 m + 3 n = n m 2 ⇒ ( 3 n + 2 m ) ( 2 n − m ) = 0
2 n = m ⇒ 2 × 3 x = 2 x ⇒ x = lo g 2 3 2 1
a = 2 3 , b = 2 1
a + b = 2 3 + 2 1 = 2
lo g 2 ( 2 x − 1 + 3 x + 1 ) = 2 x − lo g 2 ( 3 x )
l o g 2 ( 2 x − 1 + 3 x + 1 ) = 3 x 2 2 x
2 x − 1 + 3 x + 1 = 3 x 2 2 x
2 x ( 2 1 + 3 2 x 3 x ) = 3 x 2 2 x
2 1 + 3 2 x 3 x = 3 x 2 x
2 1 + 3t = t 1
2 t 6 t 2 + t − 2 = 0
t = 2 1
2 3 x = 2 1
x = lo g 2 3 ( 2 1 ))
Problem Loading...
Note Loading...
Set Loading...
lo g 2 ( 2 x − 1 + 3 x + 1 ) + lo g 2 ( 3 x ) = 2 x
Now let n = 2 x and let m = 3 x .
Using Properties of logs, we have that
m n + 6 m 2 = 2 n 2 .
Now divide By mn and let n m = t .
1 + n 6 m = m 2 n n m = t 6 t 2 + t − 2 = 0 t = 2 1 o r t = − 3 2 ( rejected because t must be positive ) ⇒ t = 2 1 x = lo g 2 3 lo g 2 1 = lo g 3 / 2 ( 1 / 2 ) a + b = 2 1 + 2 3 = 2 .